Eksperimentasi Pembelajaran Matematika Dengan Model Pembelajaran Pendidikan Matematika Realistik Indonesia (Pmri) Dan Relating, Experiencing, Applying, Cooperating, And Transfering (React) Ditinjau Dari Kemampuan Komunikasi Matematis Siswa (Eksperimen pada Siswa Kelas X SMA Negeri 1 Wonosari, Klaten Tahun Pelajaran 2014/2015) - Wiraswanto, Muhamad; , Dra. Sri Sutarni, M.Pd; , Sri Rejeki, M.Pd, M.Sc (2015)
There are three aims of this study: (1) Evaluating the difference of student' mathematics achievement viewed from two difference learning models (PMRI and REACT). (2) Evaluating the difference of students' matheatics achievement viewed from students' mathematics communications skill. (3) Evaluating the effect of interaction between learning models (PMRI and REACT) and students' mathematics communication skill on students' mathematics achievement. This study is quantitativeresearch with quasi eksperimental design. The population of this study is 333 students of nine clusses of grade X of SMA 1 Wonosari. Two classes were chosen as the sample of this study by cluster random sampling. The data collection was conducted using test, questionaire and documentation. The data were analyzed using different number of cell analysis of variance with α = 5%. Based on the analysis, it can be concluded that: (1) There is difference on students' mathematics achievement viewed from two difference learning models (PMRI and REACT). (2) There is the difference on students' matheatics achievement viewed from students' mathematics communications skill. (3) There is no effect of interaction between learning models (PMRI and REACT) and students' mathematics communication skill on students' mathematics achievement.